Tigecycline and intravenous fosfomycin zone breakpoints equivalent to the EUCAST MIC criteria for Enterobacteriaceae - Pasteran, Fernando; Lucero, Celeste; Rapoport, Melina; Guerriero, Leonor; Barreiro, Irene; Albornoz, Ezequiel; Veliz, Omar; Corso, Alejandra (The Journal of Infection in Developing Countries, 2012)
Introduction: Tigecycline and intravenous (i.v.) fosfomycin could be alternative therapeutic options for the treatment of carbapenemase-possessing Enterobacteriaceae bacterial infections. However, routine laboratories are forced to test these drugs using minimum inhibitory concentration (MIC) methods as zone breakpoints are not available for the disc diffusion technique. Methodology: Clinical and Laboratory Standards Institute methods for agar dilution and disc diffusion were compared to determine tentative zone breakpoints that best correlate to tigecycline and i.v. fosfomycin MIC breakpoints defined by the European Committee on Antimicrobial Susceptibility Testing. A total of 195 Enterobacteriaceae with defined mechanisms of resistance were tested in duplicate assays. Half of the strains were characterized as carbapenemase producers (KPC-2, OXA-48, OXA-163, VIM-1, VIM-2, IMP-8, NDM-1). Results: Corresponding zone diameters of susceptible ≥15mm, resistant ≤12mm and susceptible ≥17mm, resistant ≤15mm for the 50µg fosfomycin plus 50µg glucose-6-phosphate and 200µg fosfomycin plus 50µg glucose-6-phosphate discs, respectively, allowed categorization of the strains with an acceptable level of error (< 10% minor errors, < 1.5 % major errors, < 1% very major errors and categorical agreement > 90%). For the 15µg tigecycline disc, the best performance was achieved with the corresponding zone diameters of susceptible ≥ 21mm and resistant ≤ 16mm, which eliminated the very major and major errors but not the minor errors (34.4%). Conclusions: Based on these results, tigecycline and fosfomycin can be included in the routine panel of antibiotics for susceptibility testing by disc diffusion to provide fast and reliable information for the selection of treatment alternatives, especially for strains with extreme resistance, as carbapenemase producers.